SAT premier 2014 - Kaplan Educational Centers (Firm : New York, N.Y.) (New York : Kaplan Pub., 2013)
Provides study tools for the SAT, including eight practice tests with detailed answer explanations, an overview of the test content and structure, test-taking tips and score-raising strategies, and access to additional tests online with video content and practice quizzes. Includes a DVD.
Cover title: SAT premier 2014.
Young Adult.
Young Adult
DVD.
Keywords: SAT (Educational test) -- Study guides; Universities and colleges -- Entrance examinations -- Study guides; Colleges and universities -- Entrance examinations -- Study guides; SAT (Educational test) -- Study guides